Ne'er duke well - Vasti, Alexandra (St. Martin's Griffin, 2024)
"In this steamy Regency romp, Lady Selina is determined to find the Duke of Stanhope the perfect wife--the only problem is she's starting to think that might be her. Peter Kent--newly inherited Duke of Stanhope and recently of New Orleans, Louisiana--must become respectable. Between his radical politics and the time he interrupted a minor royal wedding with a flock of sheep--not his fault!--he's developed a scandalous reputation at odds with his goal of becoming guardian to his half siblings. For help, he turns to the cleverest and most managing woman of his acquaintance, Lady Selina Ravenscroft. Selina is society's most proper debutante, save one tiny secret: she runs an erotic circulating library for women. When Peter asks for her help, she suggests courtship and marriage to a lady of unimpeachable reputation. (Which is to say, definitely not herself.) But matchmaking doesn't go according to plan. Peter's siblings run rampant on Bond Street. Selina ends up in the Serpentine. And worst of all, the scorching chemistry between Peter and Selina proves impossible to resist. For the disreputable duke and his unpredictable matchmaker, falling in love just might be the ultimate scandal"--